The Composition of Root-Associated Bacteria and Fungi of Astragalus mongholicus and Their Relationship With the Bioactive Ingredients - Li, Yanmei; Liu, Yang; Zhang, Hui; Yang, Yan; Wei, Gehong; Li, Zhefei (Frontiers in Microbiology, 2021)
Astragalus membranaceus (Fisch.) Bge. var. mongholicus, which is used in traditional Chinese medicine, contains several bioactive ingredients. The root-associated microbial communities play a crucial role in the production of secondary metabolites in plants. However, the correlation of root-associated bacteria and fungi with the bioactive ingredients production in A. mongholicus has not been elucidated. This study aimed to examine the changes in soil properties, root bioactive ingredients, and microbial communities in different cultivation years. The root-associated bacterial and fungal composition was analyzed using high-throughput sequencing. The correlation between root-associated bacteria and fungi, soil properties, and six major bioactive ingredients were examined using multivariate correlation analysis. Results showed that soil properties and bioactive ingredients were distinct across different cultivation years. The composition of the rhizosphere microbiome was different from that of the root endosphere microbiome.The bacterial community structure was affected by the cultivation year and exhibited a time-decay pattern. Soil properties affected the fungal community composition. It was found that 18 root-associated bacterial operational taxonomic units (OTUs) and 4 fungal OTUs were positively and negatively correlated with bioactive ingredient content, respectively. The abundance of Stenotrophomonas in the rhizosphere was positively correlated with astragaloside content. Phyllobacterium and Inquilinus in the endosphere were positively correlated with the calycosin content. In summary, this study provided a new opportunity and theoretical reference for improving the production and quality of in A. mongholicus, which thus increase the pharmacological value of A. mongholicus.